A new, other than acoustic, quantification method for endocardium detection in echocardiographic images - Wojnar, Leszek (Image analysis and stereology, 2001)
A new, semiautomatic algorithm for tracing outlines of endocardium of newbornsthat are detectable in echocardiographic images is presented. The mainadvantage of the method proposed is its low sensitivity to operator errors. Moreover, in contrast to the acoustic quantification method (AQ), an analysis of archive and low quality images is available, as well as the tracesobtained are smooth and free of artefacts. Thus, the new solution allowsfor further, fully automatic, quantitative characterization of the shapeand size of the ventricle. The results are compared with manual tracings in order to demonstrate the advantage of the newly developed method. Some results from massive research on newborns with various heart defects are also presented.
Keywords: Echocardiography; Ehokardiografija; Endocardium; Endokard; Anatomy And Histology; Slika, obdelava z računalnikom; Novorojenček; Image Processing, Computer-Assisted; Infant, Newborn; analiza slik; stereologija; diagnostika; metode; novorojenčki